ФАРМАКОЕКОНОМІЧНЕ МОДЕЛЮВАННЯ ВАКЦИНОПРОФІЛАКТИКИ COVID-19 - Соловйов, С.О.; Дзюблик, І.В.; Трохимчук, В.В.; Трохименко, О.П. (Українські медичні вісті, 2023)
ФАРМАКОЕКОНОМІЧНЕ МОДЕЛЮВАННЯ ВАКЦИНОПРОФІЛАКТИКИ COVID-19